A show of hands for the republic : opinion, information, and repression in eighteenth-century rural France - Walshaw, Jill Maciak (Changing perspectives on early modern Europe., 2014)
In 1796, Thomas Bordas was indicted for ""seditious speech"" after proposing a simple vote -- a ""show of hands""--To determine who wanted a republic, and who wanted a king. In 'A Show of Hands for the Republic', Jill Maciak Walshaw uses hundreds of similar incidents to demonstrate that 18th-century French villagers were well-informed and outspoken on political issues. In the countryside, the Revolution brought more than a superficial and short-lived exposure to national affairs; it was a critical episode in a longer process of politicization, and revealed the originality in local responses.